Cueless blindsight - Stoerig, Petra (Frontiers in Human Neuroscience, 2010)
The term blindsight describes the non-reflexive visual functions that remain or recover in fields of absolute cortical blindness. As visual stimuli confined to such fields are subjectively invisible, they are customarily announced by visible or audible cues that inform the patients when to respond. The pervasive use of cueing has spawned the widely held assumption that sight and blindsight differ in that only blindsight requires cueing. To test this assumption, we measured detection of auditorily cued and un-cued stimuli in three hemianopic patients. Stimuli fell onto the photosensitive retina of the subjectively blind field, onto the objectively blind optic disc, and, in one patient, into a region where they evoked impoverished conscious sight. Regardless of whether cues were given, performance was highly significant in the latter region of poor sight, clearly above chance in the subjectively blind field, and random in the optic disc control condition. Moreover, cues enhanced detection only in the relatively blind field. Showing that blindsight performance persists when cues are omitted, the results imply that non-reflexive responses can be initiated in the absence of both stimulus awareness and perceptible cues.